Nutrient content comparison of milk from Saanen Goat between Sandakan farm and Desa Dairy Farm - Lee, Jian Xiang (Universiti Malaysia Sabah, 2017)
An experiment was conducted at the Faculty of Sustainable Agriculture' s Final Year Project laboratories in University Malaysia Sabah, Sandakan, Sabah to determine the selected nutritional content and proximate analysis of the Saanen goat's milk. The objective is to determine the selected nutritional content (lactose and calcium) and proximate analysis of the fresh goat milk from Saanen goat the reared in the Sandakan's farm and in the Desa Dairy Farm, Ranau. Independent-samples t-test was used and done under the statistical program SPSS, version 22. Fresh milk samples from Saanen goat in Desa Dairy Farm that brought from Desa Fresh Mart in Mile 4, Sandakan was used to compare with the Saanen goat from Az-Zahra Farm that reared in Sandakan in Mile 10 (control). Parameters were included total solids/dry matter, moisture, ash, fat, protein, carbohydrates, lactose, and calcium and each of them were made in three replicates for each farm. From the result, although carbohydrates and lactose content in the Saanen goat milk from Desa Dairy Farm were higher than Az-Zahra Farm, they were no significant difference between them. However, the others nutrients (total solids/dry matter, moisture, ash, fat, protein, and calcium) had showed significant difference between the farms (p<0.05). Thus, the alternate hypothesis (HA) was accepted and the Desa Dairy Farm have the higher nutritional value for most of the nutrients except the ash content for its goat milk. Since the data analysed in this research were very limited, further indepth research on the factors affecting the milk composition are recommended. For example, the different stage of lactation or the feeding management of the Saanen goat. Besides that, dairy goat farms with the easier access to their management system for the goats are also recommended for comparison.